Approximations for the nucleation temperature of water; International Journal of Heat and Mass Transfer; Vol. 207 - Skripov P. V. Pavel; Bar-Kohany T. Tali; Antonov D. V. Dmitry Vladimirovich; Strizhak P. A. Pavel Alexandrovich; Sazhin S. S. Sergey Stepanovich (2023, 2023)
Title screen